2016
DOI: 10.5433/1679-0359.2016v37n5supl2p3673
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for bovine tuberculosis in the State of São Paulo, Brazil

Abstract: A cross sectional study was carried out between May and November 2011 to investigate the epidemiological situation of bovine tuberculosis (bTB) in the state of São Paulo, Brazil. The state was divided into seven regions. Three hundred farms from each region, with reproductive activity, were randomly chosen and included as primary sample units. A fixed number of bovine females, older than 2 years of age, were randomly selected and tested, using the comparative cervical tuberculin test. An epidemiological questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 25 publications
1
47
0
10
Order By: Relevance
“…Studies based on bovine tuberculosis, conducted in 12 Federative Units, which contain 75% of the Brazilian herd, showed herd prevalence estimates between 0.5% and 9.0% in Santa Catarina and São Paulo, respectively (BAHIENSE et al, 2016;BARBIERI et al, 2016;DIAS et al, 2016;GALVIS et al, 2016;GUEDES et al, 2016;LIMA et al, 2016;NÉSPOLI et al, 2016;QUEIROZ et al, 2016;ROCHA et al, 2016;SILVA et al, 2016;VELOSO et al, 2016;VENDRAME et al, 2016). The same authors observed that the risk of bovine tuberculosis increased in larger dairy cattle herds on farms that use some degree of automation in the dairy production process.…”
Section: Resultsmentioning
confidence: 52%
“…Studies based on bovine tuberculosis, conducted in 12 Federative Units, which contain 75% of the Brazilian herd, showed herd prevalence estimates between 0.5% and 9.0% in Santa Catarina and São Paulo, respectively (BAHIENSE et al, 2016;BARBIERI et al, 2016;DIAS et al, 2016;GALVIS et al, 2016;GUEDES et al, 2016;LIMA et al, 2016;NÉSPOLI et al, 2016;QUEIROZ et al, 2016;ROCHA et al, 2016;SILVA et al, 2016;VELOSO et al, 2016;VENDRAME et al, 2016). The same authors observed that the risk of bovine tuberculosis increased in larger dairy cattle herds on farms that use some degree of automation in the dairy production process.…”
Section: Resultsmentioning
confidence: 52%
“…The higher probability of infection in herds from properties with more animals was also verified in the Republic of Ireland (GRIFFIN et al, 1996;CLEGG et al, 2012), United Kingdom (REILLY; COURTENAY, 2007;RAMÍREZ-VILLAESCUSA et al, 2010;BESSELL et al, 2012), New Zealand (PORPHYRE et al, 2008), and Brazil (BAHIENSE et al, 2016DIAS et al, 2016;GALVIS et al, 2016;SILVA et al, 2016;BAUMGARTEN et al, 2016). Larger herds present greater replacement rates, increasing the risk of inclusion of infected animals.…”
Section: Discussionmentioning
confidence: 91%
“…Dairy herds are more vulnerable to tuberculosis because dairy production involves animal confinement during milking, which increases the risk of transmission (BARLOW et al, 1997), considering that confinement increases the population density and consequently the probability of infectious contacts (HUMBLET et al, 2010;ALVAREZ et al, 2012). Dairy herds also presented greater risk for tuberculosis in New Zealand (PORPHYRE et al, 2008), United Kingdom (RAMÍREZ-VILLAESCUSA et al, 2010;KAROLEMEAS et al, 2011), andBrazil (BAHIENSE et al, 2016;BARBIERI et al, 2016;DIAS et al, 2016;GALVIS et al, 2016;ROCHA et al, 2016;SILVA et al, 2016;BAUMGARTEN et al, 2016). Furthermore, dairy cattle tend to be older than beef cattle and consequently, have a greater probability of exposure to the infectious agent (HUMBLET et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extensive and systematic employment of milk pasteurization has significantly reduced the incidence of these diseases in the human population (SINHA, 1994). However, in countries such as Brazil, where these diseases are still currently widespread in herds (BRASIL, 2006a) and the consumption of dairy products prepared with raw milk persists (SOUSA, 2005; ROCHA et al, 2014), it is reasonable to accept the occurrence of human cases by this route of transmission, despite the lack of Brazilian epidemiological data corroborating this hypothesis.A recent study carried out in 13 Brazilian states, which hold 75% of the country cattle population, showed the prevalence of tuberculosis infected herds ranging from 0.36% in the Federal District to 9.0% in São Paulo (BAHIENSE et al, 2016;BARBIERI et al, 2016;DIAS et al, 2016b;GALVIS et al, 2016;GUEDES et al, 2016;LIMA et al, 2016;NÉSPOLI et al, 2016;QUEIROZ et al, 2016;RIBEIRO et al, 2016;ROCHA et al, 2016;SILVA et al, 2016a;VELOSO et al, 2016;VENDRAME et al, 2016). In relation to bovine brucellosis, 18 Brazilian states were recently studied, comprising 85% of the country cattle population, and the prevalence ranged from 0.91% in Santa Catarina to 30.6% in Mato Grosso do Sul ALVES et al, 2009;ANZAI et al, 2016;BARDDAL et al, 2016;BAUMGARTEN et al, 2016; BORBA et al, 2013; CLEMENTINO et al., 2016;DIAS et al, 2009;DIAS et al, 2016a;INLAMEA et al, 2016;KLEIN-GUNNEWIEK et al, 2009;LEAL FILHO et al, 2016;OGATA et al, 2009;OLIVEIRA et al, 2016;ROCHA et al, 2009; SILVA et al, 2016b;SILVA et al, 2009).…”
mentioning
confidence: 99%